IMPLEMENTATION OF DECISIONINVEST IN CAPITAL MARKET TOLABORATORY OF FINANCIAL AND CAPITAL MARKET STUDY PROGRAM MANAGEMENT - Hasa Nurrohim KP; C. Ambar Pujiharjanto; Sri Isworo Ediningsih (Universitas Lambung Mangkurat, 2020)
This research carried out to look back at investment decisions made by the academic community within the Management Study Program UPN